Concentration, chemical composition and toxicological responses of the ultrafine fraction of urban air particles in PM1. (December 2022) - Yang, Mo; Wu, Qi-Zhen; Zhang, Yun-Ting; Leskinen, Ari; Komppula, Mika; Hakkarainen, Henri; Roponen, Marjut; Xu, Shu-Li; Lin, Li-Zi; Liu, Ru-Qing; Hu, Li-Wen; Yang, Bo-Yi; et al.
Graphical abstract: Highlights: High number concentration and toxicity of ultrafine particles cannot be ignored. Monitoring the number concentrations of small particles is important. Mono-culture exposure to PM may underestimate the true PM toxicity. Abstract: Epidemiological and toxicological evidence show that PM1 is a key driver of PM2.5 . However, the particle sizes that play the major damaging role in PM1 is unclear. Our aims were to (1) explore the concentration and chemical composition of ultrafine particles in PM1 ; (2) evaluate and compare the differences in toxicity of PM1-0.2 and PM0.2 to different airway cell models. We collected PM1-0.2 and PM0.2 in Guangzhou in December 2017, monitored and detected their concentrations, size, and components. A549, THP-1 mono-cultures and A549/THP-1 co-cultured cells were exposed to PM1-0.2 and PM0.2, and evaluated for toxicological responses. PM0.2 contributed to15% PM1 mass and 87.67% to particle number (PN). Most of PM0.2 was PM0.1 (exceed 75%). Structure of particles in PM0.2 were mostly spherical, whereas in PM1-0.2 they were more diverse. Within the same mass unit, PM0.2 contained more chemical components than PM1-0.2 ; within the same volume, a higher mass of components was found in PM1-0.2 . IL-6 and IL-8 were secreted by co-cultured cells in higher manner compared to mono cell cultures. PM0.2 -induced higher toxicological responses compared to PM1-0.2 . Our findings suggest that high PN concentration and toxicity of ultrafine or PM1 cannot be ignored. Mono-cell culture may underestimate the true PM toxicity.